PENDIDIKAN TINGGI KADER MUHAMMADIYAH: Pengalaman Pondok Muhammadiyah Hajjah Nuriyah Shabran UMS - Hidayat, Syamsul (Tajdida, 2015)
This paper is intended to describe the experience of organizing the Shabran Boarding(designation for the Muhammadiyah Hajjah Nuriyah Shabran Boarding UMS) as a center of higher education of Muhammadiyah cadres under the direct guidance by Muhammadiyah. With a historical approach narrative of this paper describes the development of Shabran Boarding UMS as far as can be covered by the author, so it will be able to take some important points for the development of Shabran boarding in forward. Shabran Boarding trip with all its dynamics has undergone four phases of development. The first phase (1982-1992) cottage really only manage student cadre official delegation PWM / PWA throughout Indonesia. The second phase (1993-1997), Shabran changed, it is no longer a function of forging the cadre official delegation PWM / PWA, but only as a dormitory with religious education in addition to the interest in religious sciences from various faculties and departments. But in its development corrected by receiving back the messenger Muhammadiyah cadres with 50% scholarship for students of Islamic studies. The third phase (1998-2005) as a continuation of the second phase with some development, namely the separation of the two groups of students Islamic faculty and vice versa. The fourth phase (2007-present), Shobran Boarding back to khittah to receive an official delegation of PWM, is integrated with the faculty of Islamic faculty UMS, and special for boy students.